Estudo das propriedades magnéticas de matrizes de sílica e titânia dopadas com manganês através do método sol-gel - Silveira, João Matheus de Oliveira (2009)
The search for materials that support the many conditions imposed on electronic devices for computers and other systems, come to turning more and more intense. This way, materials sensitive to variables magnetic fields, resistant to abrupt variations of temperatures are being quite longed for. Several methods for preparation of samples have been used. Their great majority is based on mechanical systems of mixture and usually accomplished in temperatures significantly discharges. The sol-gel method, for allowing a direct control to all their stages, appears very promising. Matrices of silicon oxide and titanium oxide were doped with chloride of manganese to get materials with paramagnetic phase, being this identified from results originating from relationships between the magnetic susceptibility and the temperature, obtained through measures done and in a superconducting quantum interferometer device (SQUID) that, presents a big sensibility to magnetic fields of low intensities for temperature. Key words: spin; sol-gel method; paramagnetism; SQUID magnetometry.